A Debate Programme "Máte slovo" as an Environment for a Clash of the Communicants' Roles - Svobodová, Jindřiška (Bohemica Olomucensia, 2017)
The media environment hosts many topics belonging to the cultural, social and political discourses. The recent media communication concerning the political discourse is characterized by widening the range of participants invited to take part in the debate on current political issues. Besides professional politicians there are so-called present-day politicians (i.e. the representatives of non-governmental, human rights or ecologic organisations) the economists, financial experts or experts in any key topics in question, and finally, there are representatives of the public.The author pursues how the medium may influence the presentation of an issue through the choice of the debate participants and their respective roles within the programme, thus influencing, persuading and at the worst manipulate the prospective recipient.
Keywords: media communication; political/media discourse; debate participants; persuasion and manipulation